2014
DOI: 10.5489/cuaj.1811
|View full text |Cite
|
Sign up to set email alerts
|

Renal collision tumour of papillary cell carcinoma and chromophobe cell carcinoma with sarcomatoid transformation: A case report and review of the literature

Abstract: The simultaneous occurrence of different histological types of adjacent neoplasms in the same organ is called a collision tumour, and rarely occurs in the kidney. A 63-year-old female presented to the urology department with a 1-month history of a painless hematuria. The computed tomography scans of the abdomen revealed 2 heterogeneous incidental right renal masses. The patient underwent radical nephrectomy including lymphadenectomy without adjuvant therapy. Histopathological examination showed a type 2 renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…The earliest case was reported by Graves and Templeton (12) in 1921, and the most recent one was reported by Atilgan et al (2) in 2013. According to Pubmed search results, ~40 cases of synchronous ipsilateral RCC and renal pelvic UC have been reported in the literature to date (2,3,14,15). The average age of the reviewed patients was 65±11 years; the male/female ratio was 1.6; and the left-to-right-side ratio was 1.9.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The earliest case was reported by Graves and Templeton (12) in 1921, and the most recent one was reported by Atilgan et al (2) in 2013. According to Pubmed search results, ~40 cases of synchronous ipsilateral RCC and renal pelvic UC have been reported in the literature to date (2,3,14,15). The average age of the reviewed patients was 65±11 years; the male/female ratio was 1.6; and the left-to-right-side ratio was 1.9.…”
Section: Discussionmentioning
confidence: 97%
“…The average age of the reviewed patients was 65±11 years; the male/female ratio was 1.6; and the left-to-right-side ratio was 1.9. In total, 73% of the cases presented with hematuria, 37% with flank pain and 10% without obvious symptoms, and no identifiable past medical history could be observed (2,3,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a papillary component within renal oncocytic tumors is often underestimated and, in case, simply regarded as a collision tumor. This type of renal collision tumors has been widely described in case reports as histological findings [ 5 , 11 ]. A recent report investigated the phenotypic and cytogenetic features of these lesions, concluding that the two histological counterparts are different and should be considered colliding neoplasms [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A collision tumor is defined as the coexistence of 2 adjacent but histologically distinct and independent malignant tumors in the same thyroid, without histological admixture [10]. Collision tumors can occur in various organs such as the ovaries, colon, lung, stomach, skin, and kidneys, but they are extremely rare in the thyroid [11]. It has also been suggested that each malignant component should be treated as an independent primary tumor [12].…”
Section: Discussionmentioning
confidence: 99%